The role of the sports kinesiologist to prevent grade II Ankle sprains in volleyball - D'Isanto, T.; Esposito, G.; Ceruso, R.; D'Elia, F.; Raiola, G. (European Journal of Human Movement, 2024)
In sports such as volleyball, characterized by repetitive high-intensity movements that heighten the risk of musculoskeletal injuries, particularly to the ankle, critical management of diagnosis, rehabilitation, and re-athletisation phases by specialized professionals comes to the forefront. In the realm of sports medicine and rehabilitation, there is a growing need to comprehensively assess the effectiveness of various professionals involved in the recovery process after injuries. The validity of such evaluations can only be established through prospective studies that follow individuals` post-injury. This study aims to evaluate the effectiveness of sports kinesiologists in ankle injury rehabilitation through the lens of athlete perception. By establishing valid relationships between recovery outcomes and the professionals involved, this research seeks to provide valuable insights into the world of sports rehabilitation. To attain a comprehensive understanding, qualitative data were collected and analyzed. Surveys were administered to 52 volleyball athletes (27 males and 25 females), all of whom had experienced at least one Grade II Ankle Sprains injury during their athletic careers. The survey questions encompassed aspects such as weekly training frequency, engagement in preventive exercises, the number of career injuries, injury recurrence events and knowledge of the kinesiologist. The Chi-Square test identified a significant correlation between reduced injury relapse and regular engagement in preventive exercises (p < 0.05). This study emphasizes the importance of sports kinesiologists in the context of volleyball injury prevention, highlighting the necessity of customizing protocols to cater to individual athletes' needs and preferences. It clarifies the distinction between the standard protocols of athletic trainers and the specific protocols of kinesiologists specializing in preventive and adapted physical activities. This study contributes to clarifying the professional role of preventive and adapted physical activities kinesiologists, setting them apart from other professionals working in the realm of sports training.